New Orleans sports : playing hard in the Big Easy - Aiello, Thomas, 1977- (Sport, culture & society (University of Arkansas Press), 2019)
"New Orleans was and is a city fixated on its own history and culture. Founded in 1718 by the French, transferred to the Spanish in the Treaty of Paris in 1763, and sold to the United States in 1803, the city's culture, law, architecture, food, music, and language share the influence of all three countries. This cultural mélange also manifests in the city's approach to sport, where each game seems steeped in the city's history. Tracing that history from the early nineteenth century to the late twentieth century, while also surveying the state of the city's sports historiography, New Orleans Sports places sport in the context of race relations, politics, and civic and business development to expand the historiography--currently dominated by a text that stops at 1900--into the twentieth century, offering a modern examination of sports in the city"--